LOW BITRATE HYBRID SECURED IMAGE COMPRESSION FOR WIRELESS IMAGE SENSOR NETWORK - G, SUSEELA; Y, ASNATH VICTY PHAMILA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Wireless image sensor networks are capable of sensing, processing and transmitting the visual data along with the scalar data and have attained wide attention in sensitive applications such as visual surveillance, habitat monitoring, and ubiquitous computing. The sensor nodes in the network are resource constrained in nature. Since the image data are huge always high computational cost and energy budget are levied on the sensor nodes. The compression standards JPEG and JPEG 2000 are not feasible as they involve complex computations. To stretch out the life span of these nodes, it is required to have low complex and low bitrate image compression techniques exclusively designed for this platform. The complicated scenario of wireless sensor network in processing and transmitting image data has been addressed by a low complex hybrid secured image compression technique using discrete wavelet transform and Bin discrete cosine transformation. Â Â 